Lighting up Individual Organelles With Fluorescent Carbon Dots - Liu, Haifang; Guo, Jiancheng; Aryee, Aaron Albert; Hua, Linlin; Sun, Yuanqiang; Li, Zhaohui; Liu, Jianbo; Tang, Wenxue (Frontiers in Chemistry, 2021)
Cell organelles play crucial roles in the normal functioning of an organism, therefore the disruption of their operation is associated with diseases and in some cases death. Thus, the detection and monitoring of the activities within these organelles are of great importance. Several probes based on graphene oxide, small molecules, and other nanomaterials have been developed for targeting specific organelles. Among these materials, organelle-targeted fluorescent probes based on carbon dots have attracted substantial attention in recent years owing to their superior characteristics, which include facile synthesis, good photostability, low cytotoxicity, and high selectivity. The ability of these probes to target specific organelles enables researchers to obtain valuable information for understanding the processes involved in their functions and/or malfunctions and may also aid in effective targeted drug delivery. This review highlights recently reported organelle-specific fluorescent probes based on carbon dots. The precursors of these carbon dots are also discussed because studies have shown that many of the intrinsic properties of these probes originate from the precursor used. An overview of the functions of the discussed organelles, the types of probes used, and their advantages and limitations are also provided. Organelles such as the mitochondria, nucleus, lysosomes, and endoplasmic reticulum have been the central focus of research to date, whereas the Golgi body, centrosome, vesicles, and others have received comparatively little attention. It is therefore the hope of the authors that further studies will be conducted in an effort to design probes with the ability to localize within these less studied organelles so as to fully elucidate the mechanisms underlying their function.